PENGARUH LAMA PENYIMPANAN, SUHU DAN LAMA PENGERINGAN KENTANG TERHADAP KUALITAS KERIPIK KENTANG PUTIH [Effect of Storage, Temperature and Drying Duration of Potato on Potato Chip Quality] - Ali Asgar; Asih Kartasih; Asep Supriadi; Henna Trisdyani (BERITA BIOLOGI, 2010)
The purpose of this research was to study storage duration of potato, temperature and drying duration on the quality of Granola potato chips.This research was conducted at Postharvest Laboratory of Indonesian Vegetable Research Institute from May to November 2009. A Randomized Complete Block Design was used with two replications. First factor was storage duration of potato: 1 day, 4 and 7 days. Second factor was temperature: 40°C, 50°C and 60°C. Third factor was drying duration (16, 18, and 20 hours). The result showed that storage period of 1 day, drying temperature at 50°C for 20 hours gave the best quality of potato chip with better consumer preference. Good storage period of raw material, drying condition with appropiate temperature and time of drying could produce good quality of potato chip.